2005
DOI: 10.1149/1.1869292
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Conformal ALD of SrTiO[sub 3] Thin Films Using Conventional Metallorganic Precursors

Abstract: SrTiO 3 ͑STO͒ thin films were grown on Si wafer, Pt-and Ru-coated Si wafers, respectively, by an atomic layer deposition ͑ALD͒ technique using conventional metallorganic precursors, Sr͑C 11 H 19 O 2 ͒ 2 ͑Sr͑thd͒ 2 ͒ and Ti͑Oi-C 3 H 7 ͒ 4 ͑TTIP͒ as Sr-and Tiprecursors, respectively, with a remote-plasma activated H 2 O vapor as the oxidant at a wafer temperature of 250°C. Patterned Si wafers with contact holes having a diameter of 0.13 and 1 µm depth ͑aspect ratio of 8͒ was used in order to test the film-thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
80
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 34 publications
2
80
0
Order By: Relevance
“…There are peaks that originated from Ru-O bonding as well as Ru-Ru bonding. Furthermore, we can identify RuO 2 16 from the shift in these peaks. Thus, we found that RuO 2 was formed at the surface of the Ru electrode.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are peaks that originated from Ru-O bonding as well as Ru-Ru bonding. Furthermore, we can identify RuO 2 16 from the shift in these peaks. Thus, we found that RuO 2 was formed at the surface of the Ru electrode.…”
Section: Resultsmentioning
confidence: 99%
“…• C, the vapor pressures of strontium such as Sr(thd) 2 are insufficient being less than 1 Torr. 2 Therefore, it is still difficult to commercialize SrTiO 3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The most common volatile precursors of strontium were synthesized using β-diketonates like 2,2,6,6-tetramethyl-3,5-heptanedione 7,8 and highly substituted cyclopentadienes.…”
mentioning
confidence: 99%
“…86 Oxygen transport studies have also been reported for Pt and Re protective layers, considered also as bottom gate electrodes for MOS-like devices. 87,88,89 In the case of gate dielectric layers for CMOS and memory (DRAM) devices, several (usually high-K) binary oxides such as Ta2O5, 90,91 Y2O3, 92,93 Al2O3, 91,94,95,96 HfO2, 97,98,99,100 ZrO2, 34,101,102,103 and TiO2, 104,105,106 and also perovskite materials such as SrTiO3 and (Ba,Sr)TiO3 have been investigated, 107,108 according to their electrical and/or other physical properties after/or during growth. Apart from the characterization of the grown layers, in some of these oxide studies, oxygen diffusion through the gate dielectric towards deeper layers has also been investigated.…”
Section: Current Status 1231 Microelectronic (Dram and Cmos) Devicesmentioning
confidence: 99%